2020
DOI: 10.15586/jptcp.v27isp1.757
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting of COVID-19 infections in E7 countries and proposing some policies based on the Stringency Index

Abstract: COVID-19 infection data of Emerging 7 (E7) countries, namely Brazil, China, India, Indonesia, Mexico, Russia, and Turkey were described by an empirical model or a special case of this empirical model. Near-future forecasts were also performed. Moreover, the causalities between the Stringency Index’s indicators and total cases in E7 countries in COVID-19 period were examined. Countries were grouped as “stationary,” “transition,” and “exponential” based on the data and model fits. The proposed models produced go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…In this study, we also found that countries with the most disadvantaged communities, vulnerable health system, and less resources (including health system as well water and sanitation) were associated with more COVID-19 cases in BRICS countries. Our results were consistent with previous findings [6,20]. It supported the evidence that socio-economic vulnerability might have impact on the disproportionate burden on states and municipalities.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we also found that countries with the most disadvantaged communities, vulnerable health system, and less resources (including health system as well water and sanitation) were associated with more COVID-19 cases in BRICS countries. Our results were consistent with previous findings [6,20]. It supported the evidence that socio-economic vulnerability might have impact on the disproportionate burden on states and municipalities.…”
Section: Discussionsupporting
confidence: 93%
“…Rocha et al [6] found that the initial spread of COVID-19 infections in the country was most affected by patterns of socio-economic vulnerability rather than population age structure and prevalence of existing chronic diseases. Kayral et al [20] reported the association between the policy stringency and total cases in E7 countries during the COVID-19 period. In this study, we also found that countries with the most disadvantaged communities, vulnerable health system, and less resources (including health system as well water and sanitation) were associated with more COVID-19 cases in BRICS countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pre-lockdown (30 January to 24 March 2020), lockdown (25 March to 31 May 2020), unlock (1 June 2020 to 10 February 2021), second-wave (11 February to 31 May 2021). The stringency index is a composite measure based on nine response indicators including school closures, workplace closures, and travel bans, rescaled to a value from 0 to 100 (100 = strictest) ( Kayral and Buzrul, 2020 ; Royo, 2020 ). It provides an image of the phase at which any country imposed its strongest measures ( Sulyok and Walker, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Este índice mide el nivel de restricción de las políticas de contención y de cierre aplicadas en cada país durante la pandemia, combinando nueve indicadores: cierre de escuelas, cierre de lugares de trabajo, cancelación de eventos públicos, restricciones a las reuniones, cierre del transporte público, campañas de información pública, confinamiento domiciliario, restricciones a los desplazamientos internos y controles de viajes internacionales. Este índice está siendo muy útil para evaluar la efectividad de las políticas públicas puestas en marcha por los gobiernos de los distintos países o territorios, permitiendo la comparación entre ellos (3) .…”
Section: Introductionunclassified